LvCSN5 is involved in WSSV infection via interaction with wsv006. (January 2021) - Zou, Rui-Feng; Cai, Miao; Liu, Qing-Hui
Abstract: As an extremely virulent pathogen, white spot syndrome virus (WSSV) greatly threatens shrimp aquaculture worldwide. The interaction between virus and host is important for viral infection. In the present study, a yeast two-hybrid (Y2H) library was constructed to clarify the functions of wsv006, and the interaction between wsv006 and shrimp Litopenaeus vannamei ( L. vannamei ) was analyzed. Furthermore, we explored the role of the wsv006-interacting molecule L. vannamei COP9 constitutive photomorphogenic-like protein subunit 5 ( LvCSN5 ) in WSSV infection. Y2H assay showed that wsv006 interacted with LvCSN5, and co-immunoprecipitation (Co-IP) assay confirmed such interaction. Multiple alignments of amino acid sequences with other species revealed that the LvCSN5 had high identity with Penaeusmonodon CSN5 ( PmCSN5 ). LvCSN5 was mainly expressed in intestine, eye and hepatopancreas. In addition, the relative expression of LvCSN5 was significantly up-regulated both in intestine and hepatopancreas following the WSSV challenge. Besides, the relative expressions of IE1 and VP28, as well as the viral copy numbers were significantly increased in the LvCSN5 -silenced shrimp. Our findings suggested that LvCSN5 was involved in WSSV infection by interacting with wsv006. Highlights: Wsv006 interacted with LvCSN5 . LvCSN5 was mainly expressed in intestine, eye and hepatopancreas. LvCSN5 was significantly up-regulated following WSSV challenge. IE1, VP28 and viral copy numbers were significantly increased in the LvCSN5 -silenced shrimp.